The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1038/sj.onc.1209244
|View full text |Cite
|
Sign up to set email alerts
|

Short-term induction and long-term suppression of HPV16 oncogene silencing by RNA interference in cervical cancer cells

Abstract: RNA interference-mediated gene silencing has the potential to block gene expression. A synthetic double-stranded small interfering RNA (siRNA) based on a sequence motif of 21 nucleotides from human papillomavirus 16 (HPV16) E6E7 bicistronic RNA was found to be a potent siRNA that suppresses expression of both the E6 and E7 oncogenes in HPV16þ CaSki and SiHa cells. When stably expressed as a short hairpin RNA in these cells, however, siRNA silencing of E6 and E7 expression was efficient only at early cell passa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 49 publications
6
39
0
Order By: Relevance
“…20 and our data above demonstrated that shRNA delivered by lentivirus was also short-lived. One strategy to overcome this issue is the multi-copy or multi-target approach, which allows additive or even synergistic effects to induce rapid cell death before resistance occurs.…”
Section: Short-lived Rnai In Hela Cellsmentioning
confidence: 70%
See 3 more Smart Citations
“…20 and our data above demonstrated that shRNA delivered by lentivirus was also short-lived. One strategy to overcome this issue is the multi-copy or multi-target approach, which allows additive or even synergistic effects to induce rapid cell death before resistance occurs.…”
Section: Short-lived Rnai In Hela Cellsmentioning
confidence: 70%
“…18,19 In addition to the above issue, cervical cancer cell lines CaSki and SiHa have been reported to be able to develop resistance to RNAi through the expression of a previously unknown 50 kDa cytoplasmic protein that specifically interacted with the unwound antisense strand of E7 siRNA from the RNA-induced silencing complex. 20 However, this specific interaction was not observed in lamina A/C gene. Therefore the authors considered this was a cellular protection reaction to E7 as it is essential for the cell to survive.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Total RNAs were purified at 24 h after transfection. Small RNAs were then gel purified and cloned by using the adapter ligation method (26). Approximately 100 g of total RNA from transfected or infected cells was separated on a 12% denaturing PAGE gel before transfer to a membrane and hybridization with 32 P-labeled oligonucleotide probes as described previously (26).…”
Section: Methodsmentioning
confidence: 99%